Vampire nostalgia. Issue 2 (4th March 2021) - Howell, Amanda
ABSTRACT: Nostalgia ( nostos 'return home' plus algia 'longing'), first diagnosed and named in the seventeenth century, was a disease that, as Svetlana Boym points out, became less curable and more mysterious in its pathology as time passed, resistant to reason and Enlightenment in the eighteenth and nineteenth centuries. As an 'historical emotion' that 'came of age' with Romanticism and mass culture, nostalgia has continued to spread in this century, shaping aspects of everyday life from pop cultural entertainments to national politics. Emphasizing Dracula and its adaptations and shifting away from a more common focus on sex or romance as the source of vampiric appeal, this discussion argues for the role that nostalgic desires, seductions and illusions play in our relationship with one of popular culture's most enduring monsters. Focused on how vampire fictions have fed upon what Boym sums up as 'an affective yearning for a community with collective memory' and 'a longing for continuity in a fragmented world', this essay concerns itself with the narrative, aesthetic, material and cultural manifestations, and the ideological investments, of vampire nostalgia.